2002
DOI: 10.1038/sj.sc.3101254
|View full text |Cite
|
Sign up to set email alerts
|

Experimental modelling of human spinal cord injury: a model that crosses the species barrier and mimics the spectrum of human cytopathology

Abstract: Study design: Literature review and presentation of an experimental model of human spinal cord injury, (SCI). Objectives: Experimental designs seek to mimic and model the physical processes by which human SCI occurs and replicate the variety of chronic pathologies that characterize its long term e ects. The variations in biological processes that are present between species have contributed to recent di culties in generalizing experimental ®ndings to the human condition. In this review, one ®nds: (1) a discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 30 publications
(16 reference statements)
2
47
1
Order By: Relevance
“…8B); these differences may be associated with the different pathophysiological responses between species or even between strains of a given species. [46][47][48] Our results are in accord with the increasingly accepted role for Wnts in the modulation of fundamental aspects of the homeostasis and neuronal function of the adult CNS. 14,17,18,[49][50][51][52][53] In this line of thought, we provide supporting evidences of previous reports describing the expression of most Wnt ligands and receptors by PCR 39 and in situ hybridization analysis, 35 as well as a constitutive active b-catenin-mediated transcription in the dorsal horns and the central canal of the adult spinal cord of mice.…”
Section: Discussionsupporting
confidence: 78%
“…8B); these differences may be associated with the different pathophysiological responses between species or even between strains of a given species. [46][47][48] Our results are in accord with the increasingly accepted role for Wnts in the modulation of fundamental aspects of the homeostasis and neuronal function of the adult CNS. 14,17,18,[49][50][51][52][53] In this line of thought, we provide supporting evidences of previous reports describing the expression of most Wnt ligands and receptors by PCR 39 and in situ hybridization analysis, 35 as well as a constitutive active b-catenin-mediated transcription in the dorsal horns and the central canal of the adult spinal cord of mice.…”
Section: Discussionsupporting
confidence: 78%
“…The injury to the spinal cord found in our study in piglets with traumatic SCI is similar to that reported in other animal models of SCI, as well as in individuals with SCI (65)(66)(67). The pathology of complete or irreversible SCI invariably involves disruption of fiber tracts and spinal cord tissue through the thickness of the spinal cord, whereas incomplete SCI has intact fiber tracts passing through the injury zone.…”
Section: Review Of Animal Modelssupporting
confidence: 74%
“…30,31 The histopathology correlates positively with the biomechanical impact. 32 Lesion cavity Typically, the contusion SCI model is characterized by a central haemorrhagic necrosis that spreads radially and rostrocaudally, resulting in an ellipsoidal, loculated cystic cavity. The cavity is filled with macrophages and lined by activated astrocytes.…”
Section: Experimental Modelsmentioning
confidence: 99%